Cultivating The Entrepreneurial Soul of Students in Vocational High Schools (SMKN) 5 Kendari Through Training on Utilization of Cassava Skin Waste into Cassava Skin Chips - Dhian Herdhiansyah; Asriani (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
The purpose of this activity is how to grow the entrepreneurial spirit of students in the 5th Vocational High School (SMKN) Kendari through training in the utilization of cassava peel waste into cassava peel chips. The implementation of this activity is carried out in 3 stages: (1) socialization; (2) providing material on entrepreneurship motivation, the process of utilizing cassava peel waste into cassava peel chips, and how to design packaging labels by utilizing ICT; and (3) training through direct practice. Theorizing activities are carried out by lecturing and interactive discussion methods, while the cassava skin waste processing training is carried out by the demonstration method. Based on the results of activities with partners showed significant progress: (a) students' understanding and interest in entrepreneurship increased by 80%, (b) students' understanding and knowledge of cassava peel chips increased by 90%, and (c) students' understanding of how to design packaging labels with the use of ICT increased by 85%.